2012
DOI: 10.1002/glia.22306
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of transient receptor potential vanilloid 4 channel suppresses abnormal activation of microglia induced by lipopolysaccharide

Abstract: Microglia are intrinsic immune cells in the brain. In response to neurodegenerative events, excessively activated microglia change their shapes and release various cytokines leading to the pathogenesis of central nervous system (CNS) disease. Because the intracellular mechanisms of this process are still unclear, we have evaluated the functional roles of transient receptor potential vanilloid 4 (TRPV4) channel expressed in the microglia. Robust microglial activation after an injection of lipopolysaccharide (LP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 39 publications
5
50
1
Order By: Relevance
“…TRPV4-positive staining was also observed in a subpopulation of primary afferents, as reported previously (29,40,55,56). Consistent with these results, studies on glial cells of the central nervous system have demonstrated that TRPV4 is expressed by a subpopulation of astrocytes and microglia, suggesting that TRPV4 regulates Ca 2ϩ -dependent processes in glia throughout central and peripheral nervous systems (33,57,58).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…TRPV4-positive staining was also observed in a subpopulation of primary afferents, as reported previously (29,40,55,56). Consistent with these results, studies on glial cells of the central nervous system have demonstrated that TRPV4 is expressed by a subpopulation of astrocytes and microglia, suggesting that TRPV4 regulates Ca 2ϩ -dependent processes in glia throughout central and peripheral nervous systems (33,57,58).…”
Section: Discussionsupporting
confidence: 89%
“…Cultured DRG-The expression and function of TRP ion channels has been reported in neurons and glial cell types of the central and peripheral nervous systems (6,33,34). However, TRP channel activity in SGCs has not been investigated in detail.…”
Section: Maintaining Neuron-sgc Interactions In Dissociated Andmentioning
confidence: 99%
“…Moreover, pharmacological blockade of TRPV4 channels abrogated the ability of PAs to sustain flow/pressureevoked PA constrictions. Of caution is the fact that bath application of TRPV4 channel blocker will target TRPV4 channels expressed in other cell types, such as microglia (Konno et al, 2012) and neurons (Lee and Choe, 2014). However, the observations obtained from the BAPTA experiments (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with an important role for TRPV4 channels in vesselto-astrocyte communication, both in vitro and in vivo studies showed a significant decrease in the number of responding astrocytes in the TRPV4 Ϫ/Ϫ mouse. The partial persistence of astrocytic Ca 2ϩ responses in TRPV4 Ϫ/Ϫ mice may be due to the fact that TRPV4 channels can heteromerize with TRPC1 (Ma et al, 2011) or TRPP2 (Köttgen et al, 2008 channels to form functional channels. Alternatively, and, as with NVC mechanisms, multiple other channels/receptors may contribute to this process.…”
Section: Discussionmentioning
confidence: 99%
“…injected to activate TRPV4 in vivo [25, 26]. Here, the TRPV4 agonist GSK1016790A was injected (icv.)…”
Section: Methodsmentioning
confidence: 99%